Paradoks Guru Profesional di Indonesia: Antara Standar Kompetensi dan Realitas Pendidikan - Moh Syaiful Anam; Laily Nur Affi Tafuzi; Muhammad Damanhuri; Munawir (STKIP Subang, 2026)
This article aims to analyze the disconnection between teacher professionalism policies and the empirical reality of education in Indonesia. Although various policy instruments such as certification and Teacher Professional Education (PPG) have been implemented as quality assurance efforts, pedagogical and professional competence in the field often still show stagnation. Using a qualitative method through literature study and phenomenological analysis, this research explores the structural factors that hinder professionalism, including: the asynchrony of the LPTK curriculum with classroom needs, and the low economic welfare of honorary teachers who are below the Regional Minimum Wage (UMR) standard. The results of the analysis show that low wages force teachers to fragment their focus to seek side income for survival, which in turn reduces competency standards to mere administrative formalities. This article concludes that true professionalism cannot be achieved without synchronization between competency demands and guarantees of decent living welfare.